(untitled) (Journal of Information Technology and Digital World, 2023)
The feedback management portal is an online platform designed to streamline the process of collecting, analyzing, and responding to feedback from customers, employees, and stakeholders. The portal provides a user-friendly interface for users to submit feedback, which is then automatically categorized and analyzed using machine learning algorithms. Users can track the status of their feedback and receive real-time updates on any actions taken by the organization in response to their feedback. The portal also enables organizations to generate reports and insights based on the feedback data, helping them make data-driven decisions to improve their products, services, and overall customer satisfaction. Overall, the feedback management portal provides an efficient and effective way for organizations to manage and leverage feedback to drive continuous improvement.